A lithium-sulfur battery based on a polyacid material derived electrocatalyst, and a preparation method and application thereof

CN118122379BActive Publication Date: 2026-10-27CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410232665.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-01
Publication Date
2026-10-27
Estimated Expiration
2044-03-01

AI Technical Summary

Technical Problem

然而,POM团簇通常具有低电导率且容易团聚的问题,这将限制电催化过程的电荷转移并增加反应活化能垒

Benefits of technology

(1)本发明的制备方法能够得到一种分散性好、结构稳定性好的电催化剂,该催化剂材料修饰在锂硫电池的隔膜上,能有效抑制多硫化物的穿梭效应,并催化多硫化物的转化反应,提高锂硫电池的循环稳定性和工作寿命,且由于其良好的分散性,能够获得较多的活性位点,因而具有良好的催化性能,同时由于其优异的结构稳定性,使得该催化剂在常温和高温下均具有良好的催化稳定性,因其优异的导电性和结构稳定性,因此在低温下也具有良好的催化稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118122379B_ABST
    Figure CN118122379B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a lithium-sulfur battery based on a polyacid material derived electrocatalyst, which comprises the following steps: first, using a single metal atom X to substitute a polyacid and a salt thereof to prepare a polyacid material; then, mixing a cationic linker, graphene oxide and the polyacid material in an aqueous solution to assemble, so that the polyacid material is loaded on the surface of the graphene oxide; and then, performing a hydrothermal reaction, and through solid-liquid separation, freeze-drying and low-temperature heat treatment, the lithium-sulfur battery based on the polyacid material derived electrocatalyst is obtained. The raw material of the preparation method is low in price and easy to obtain, the process is simple and the conditions are mild, and the electrocatalyst with good dispersity and structural stability can be prepared; the good dispersity enables the electrocatalyst to have good catalytic performance, and the excellent structural stability enables the electrocatalyst to have good catalytic stability; and the catalyst material can be modified on the diaphragm or the positive electrode of the lithium-sulfur battery, so that the cycle stability and service life of the lithium-sulfur battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst materials technology, specifically relating to a polyacid-derived electrocatalyst for lithium-sulfur batteries, its preparation method, and its application. Background Technology

[0002] In the field of energy storage, lithium-sulfur batteries are favored due to their high energy density (2600 Wh·kg⁻¹). -1 Theoretical specific capacity (1675 mA·hg) -1 ), gravimetric energy density (2500 Wh·kg) -1 ) and volumetric energy density (2800 Wh·L) -1 Lithium-sulfur batteries have attracted widespread attention and are considered one of the most promising next-generation energy storage systems. However, problems such as sluggish electrode reaction kinetics, low sulfur utilization, uneven lithium deposition, and shuttle effect hinder their practical application in production. Developing and utilizing catalyst materials as different components of lithium-sulfur batteries (including cathode supports, separators, intermediate layers, and electrolyte additives) can accelerate electrode reaction kinetics, promote polysulfide conversion, and improve the cycle stability and service life of lithium-sulfur batteries.

[0003] The cost and intrinsic activity of catalysts are the primary considerations for developing energy storage systems. Common catalysts in lithium-sulfur batteries (mainly including metal-based and non-metal-based catalysts) have certain catalytic advantages; however, only a few active components can act on the catalytic process, and most reactions occur on the catalyst surface. Catalytic activity depends on the surface state of the catalyst rather than the internal atomic sites, and catalytic efficiency largely depends on the adsorption and desorption rates of reactants and the size of catalyst particles.

[0004] Polyoxometalates (POMs) are metal oxide anionic clusters with well-defined atomic structures. Current research has demonstrated that POMs exhibit strong catalytic effects on oxygen and sulfur compounds. However, POM clusters typically suffer from low electrical conductivity and are prone to aggregation, which limits charge transfer in electrocatalytic processes and increases the activation energy barrier of the reaction. Summary of the Invention

[0005] To address the above problems, this invention provides electrocatalysts derived from polyacid materials for lithium-sulfur batteries, their preparation methods, and applications.

[0006] To achieve the above objectives, the present invention provides the following specific technical solutions: This invention employs a novel method to synthesize electrocatalysts derived from polyacid materials. By controlling the synthesis process, catalysts with good dispersibility and structural stability can be obtained, thus exhibiting excellent catalytic performance. Furthermore, the loading of metal atoms in the catalyst material can be easily controlled while maintaining its good dispersion.

[0007] This invention provides a method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries, comprising: first, substituting a polyacid or polyacid salt with a single metal atom X to prepare a polyacid material; then, assembling the polyacid material with graphene oxide and graphene oxide in an aqueous solution using a cationic linker, thereby loading the polyacid material onto the surface of graphene oxide; followed by a hydrothermal reaction; and then solid-liquid separation, freeze-drying, and low-temperature heat treatment to obtain the polyacid-derived electrocatalyst for lithium-sulfur batteries. In this technical solution, the catalyst material finally obtained by low-temperature heat treatment is a composite material of an oxide substituted with a single metal atom X, reduced graphene oxide, and a small amount of carbon.

[0008] Preferably, the anion of the single-atom substituted polyacid material is selected from [PMo]. 11 XO 40 ] n- [SiMo] 11 XO 40 ] n- [PW] 11 XO 40 ] n- 、[SiW 11 XO 40 ] n- 、[ZnW 11 XO 40 ] n- [CoW] 11 XO 40 ] n- [CuW] 11 XO 40 ] n- [P2W] 17 XO 40 ] n- [P2Mo] 17 XO 40 ] n- and [XMo6O 24 ] n- At least one of the following, wherein the cation of the polyacid material is selected from H + Li + Na + K + and NH4 + At least one of the following; the single atom X is selected from Co, Ni, Cu, Zn, Fe, Mn, Ag, Au, Pt, Pd, Ru and Ir.

[0009] Preferably, the cationic binder can be selected from at least one of dopamine, polyethyleneimine, and melamine.

[0010] Preferably, the mass ratio of the cationic binder, graphene oxide, and monoatom-substituted polyacid material is 4:4:1 to 1:1:1.

[0011] Preferably, the hydrothermal reaction temperature is 100~200℃ and the hydrothermal reaction time is 6~24 h.

[0012] Preferably, the temperature of the low-temperature heat treatment is 200~600℃; the atmosphere for heat treatment is at least one of nitrogen, argon, or a hydrogen-argon mixture. Through hydrothermal and low-temperature heat treatment, not only can the catalytic material be further dispersed, making it less prone to agglomeration, but it is also transformed into a non-agglomerated and structurally stable metal oxide supported on reduced graphene oxide. This metal oxide retains the inherent structural characteristics and properties of polyacids and ensures that agglomeration does not easily occur during subsequent catalysis. Simultaneously, the low-temperature heat treatment can also convert the cationic linker into carbon, in which graphene oxide is converted into reduced graphene oxide, further improving the structural stability of the material.

[0013] Preferably, the freeze-drying temperature is -80 to -40°C, and the freeze-drying time is 12 to 72 hours. Preferably, the assembly involves stirring or ultrasonically treating the mixed liquid; the stirring or ultrasonic treatment time is 1-2 hours.

[0014] As a general inventive concept, a polysulfide-derived electrocatalyst for lithium-sulfur batteries is also provided, prepared using the aforementioned method. The catalyst material is in the form of a powdery flocculent and can be used on the separator or cathode of a lithium-sulfur battery to suppress the shuttle effect of polysulfides, improve sulfur utilization, and achieve high performance and long cycle life in lithium-sulfur batteries.

[0015] As a general inventive concept, this invention also provides the application of the aforementioned polysulfide-derived electrocatalyst for lithium-sulfur batteries. The prepared electrocatalyst is ultrasonically dispersed in an ethanol solution to form a slurry, and then uniformly modified onto a lithium-sulfur battery separator using vacuum filtration. This catalyst material, acting on the separator, forms a special ion channel. On one hand, this ion channel selectively allows lithium ions to pass through, accelerating the migration rate of lithium ions through the separator, enhancing the diffusion efficiency of lithium ions, improving lithium utilization in the battery, and contributing to the limited dissolution and diffusion of polysulfides; on the other hand, it can inhibit the growth of polysulfides (Li2S...). n The shuttle effect promotes the conversion reaction of polysulfides, reduces the loss of effective materials in the battery, and further inhibits the growth of lithium anode dendrites, thus protecting the lithium anode, improving battery cycle and rate performance, and extending battery life.

[0016] Preferably, the areal loading of the electrocatalyst on the lithium-sulfur battery separator is 0.25~5 mg / cm³. 2 ; Preferably, the concentration of the electrocatalyst slurry is 2~20 mg / mL; Preferably, the lithium-sulfur battery separator is at least one of polyethylene (PE) separator or polypropylene (PP) separator.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the present invention can obtain an electrocatalyst with good dispersibility and good structural stability. When the catalyst material is modified on the separator of lithium-sulfur battery, it can effectively suppress the shuttle effect of polysulfides and catalyze the conversion reaction of polysulfides, improve the cycle stability and working life of lithium-sulfur battery. Due to its good dispersibility, it can obtain more active sites, thus having good catalytic performance. At the same time, due to its excellent structural stability, the catalyst has good catalytic stability at both room temperature and high temperature. Due to its excellent conductivity and structural stability, it also has good catalytic stability at low temperature.

[0018] (2) The catalyst preparation method of the present invention uses low-cost and readily available synthetic materials, simple process and mild conditions, which will not cause the collapse of polyacid molecular structure, and can effectively inhibit the aggregation of single atoms to achieve high content loading of single atoms. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a schematic diagram illustrating the preparation principle of electrocatalysts derived from polyacid materials.

[0021] Figure 2 The image shows a TEM image of the Co-MoOx / rGO / C composite material prepared in Example 1.

[0022] Figure 3 TEM image of the Co-MoOx / rGO / C composite material prepared in Comparative Example 3.

[0023] Figure 4 The cycle performance curves are for the battery assembled in Comparative Example 1.

[0024] Figure 5 The cycle performance curves are for the battery assembled in Comparative Example 2.

[0025] Figure 6 The cycle performance curve of the battery assembled in Example 1 is shown.

[0026] Figure 7 The cycle performance curves are for the battery assembled in Comparative Example 4.

[0027] Figure 8 The cycle performance curves are for the battery assembled in Comparative Example 5.

[0028] Figure 9 The cycle performance curve of the battery assembled in Example 2 is shown.

[0029] Figure 10 The images show the SEM images of the positive and negative electrodes of Comparative Example 1 and Example 1 after 200 cycles at 1C. (a) and (b) are the microscopic morphology images of the positive electrode surface of Example 1 and Comparative Example 1 after 200 cycles, respectively. (c) and (d) are the microscopic morphology images of the lithium negative electrode surface of Example 1 and Comparative Example 1 after 200 cycles, respectively.

[0030] Figure 11 Photographs of different materials reacting with Li2S6 for the same amount of time. Detailed Implementation

[0031] This invention provides a method for preparing a catalyst. First, a polyacid material is prepared by substituting a polyacid or polyacid salt with a single metal atom X. Then, an aqueous solution of the polyacid material, an aqueous solution of graphene oxide, and an aqueous solution of a cationic linker are mixed and assembled. The catalyst is then subjected to hydrothermal treatment, solid-liquid separation, drying, and low-temperature heat treatment to obtain the final product.

[0032] In some preferred embodiments of the present invention, the single metal atom X includes, but is not limited to, one of the transition metal atoms such as Co, Ni, Cu, Zn, Fe, Mn, Ag, Au, Pt, Pd, Ru, and Ir; since transition metal elements have unfilled valence d orbitals and have the same atomic electronic configuration, they can undergo the same substitution reaction.

[0033] Furthermore, in some preferred embodiments of the present invention, the polyacid anion in the polyacid or polyacid salt substituted with a single metal atom X is selected from [PMo]. 11 XO 40 ] n- [SiMo] 11 XO 40 ] n- [PW] 11 XO 40 ] n- 、[SiW 11 XO 40 ] n- 、[ZnW 11 XO40 ] n- [CoW] 11 XO 40 ] n- [CuW] 11 XO 40 ] n- [P2W] 17 XO 40 ] n- [P2Mo] 17 XO 40 ] n- and [XMo6O 24 ] n- At least one of the following, and the cation is selected from H + Li + Na + K + and NH4 + At least one of them.

[0034] Furthermore, in some preferred embodiments of the present invention, the preparation of polyacid materials by substituting polyacids and their salts with a single metal atom X can be achieved using conventional preparation methods in the art, for example, including: The polyacid material is obtained by reacting a salt solution of metal atom X (e.g., sulfate solution) with a solution of polyacid or polyacid salt (e.g., ammonium polyacid salt) and then recrystallizing.

[0035] Furthermore, when the single atom X substitutes for a polyacid or polyacid salt, the molar ratio of atom X in the salt of single atom X to the polyacid or polyacid salt is 1:1 to 3.

[0036] Furthermore, in some preferred embodiments of the present invention, the cationic binder may be selected from at least one of dopamine, polyethyleneimine, and melamine.

[0037] Furthermore, in some preferred embodiments of the present invention, the mass ratio of the cationic binder, graphene oxide, and polyacid material is 4:4:1 to 1:1:1.

[0038] Furthermore, in some preferred embodiments of the present invention, the temperature of the hydrothermal reaction is 100~200°C; and the time of the hydrothermal reaction is 6~24 h.

[0039] Furthermore, in some preferred embodiments of the present invention, the temperature of the low-temperature heat treatment is 200~600°C; and the atmosphere is at least one of nitrogen, argon, or a hydrogen-argon mixture.

[0040] Furthermore, in some preferred embodiments of the present invention, the freeze-drying temperature is -80 to -40 °C, and the freeze-drying time is 12 to 72 h.

[0041] Furthermore, in some preferred embodiments of the present invention, the concentration of the cationic linker solution is 0.1~10 mg / ml; the concentration of the graphene oxide solution is 0.1~100 mg / ml; and the concentration of the polyacid material solution is 10~20 mg / ml.

[0042] Some embodiments of the present invention provide a polyacid-derived electrocatalyst powder for lithium-sulfur batteries, which is prepared using the aforementioned preparation method.

[0043] Some embodiments of the present invention provide an application of the aforementioned polyacid-derived electrocatalyst powder for lithium-sulfur batteries in lithium-sulfur batteries, specifically, it can be applied to the positive electrode or the separator.

[0044] When applied to the separator, the prepared electrocatalyst is ultrasonically dispersed in an ethanol solution to form a slurry, and then vacuum filtration is used to uniformly modify the catalyst material onto the lithium-sulfur battery separator.

[0045] Further, in some preferred embodiments of the present invention, the lithium-sulfur battery separator is at least one of polyethylene (PE) separator or polypropylene (PP) separator. The concentration of the catalyst slurry used to modify the separator is 2-20 mg / mL; the areal loading of the catalyst material on the lithium-sulfur battery separator is 0.25-5 mg / cm³. 2 .

[0046] To facilitate understanding of the present invention, the invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0047] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0048] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0049] Comparative Example 1 Positive electrode preparation: Ketjen black composite sulfur powder, acetylene black, and LA (LA is a water-based binder) are mixed in a mass ratio of 7:2:1, a small amount of water is added, and the mixture is ball-milled for 10 hours to obtain a positive electrode slurry. The positive electrode slurry is then uniformly coated onto a treated 12 mm aluminum foil current collector disc, with a positive electrode active material loading of 1.5-2 mg / cm³. 2 The positive electrode sheet is obtained by vacuum drying for 12 hours.

[0050] Battery Assembly: Assembly was performed in an argon-filled glove box using a CR2025 button cell casing. The positive electrode was a positive electrode sheet prepared according to the comparative example; the negative electrode was a 15.6 mm diameter lithium metal sheet; the separator was a 19 mm diameter Celgard 2500 polypropylene microporous membrane; the electrolyte was a commercial lithium-sulfur electrolyte (LS-009) at a volume of 35 μL. The battery was assembled sequentially as follows: positive electrode casing, positive electrode sheet, electrolyte, separator, electrolyte, negative electrode sheet, gasket, spring clip, and negative electrode casing. Finally, the casing was sealed using a sealing machine.

[0051] Comparative Example 2 Synthesis of catalytic material: In air, 200 mg of polyethyleneimine (PEI) was placed in a beaker containing 100 ml of water and sonicated for 30 min to dissolve, forming a PEI aqueous solution; the PEI aqueous solution was added dropwise to a beaker containing 100 ml of 2 mg / mL graphene oxide aqueous solution and stirred for 6 h; the synthesized PEI / GO solution was filtered, washed, and dissolved in 120 ml of water and sonicated for 2 h; hydrothermally heated at 180 °C for 720 min, filtered, washed, freeze-dried at -50 °C for 48 h, and then heat-treated at 600 °C under H2 / Ar atmosphere for 2 h to obtain the rGO / C composite material.

[0052] Membrane preparation: 28.26 mg of rGO composite material and 62.8 mg of LA (5% LA, mass ratio 9:1) were mixed in 10 ml of alcohol solution by sonication for 1 h. The mixture was then filtered onto a Celgard 2500 polypropylene microporous membrane with a loading of 0.5 mg / cm³. 2 Dry in an oven for 12 hours, then remove and cut into 19 mm diaphragms.

[0053] Positive electrode sheet production: Same as comparative example 1.

[0054] Battery assembly: The assembly method is the same as that of Comparative Example 1, but the separator used is the rGO / C composite separator produced in Comparative Example 2.

[0055] Example 1 Preparation of polyacid materials: 30 ml of cobalt sulfate solution (4.2 g CoSO4·7H2O, 0.015 mol) was mixed with 2 g of H2O2 (30% concentration) solution to form mixed aqueous solution A; ammonium heptamolybdate aqueous solution (containing 30.9 g...) (NH4)6Mo7O 24 (4H₂O, 0.025 mol, 260 ml water) is heated to boiling to form solution B; solution A is slowly added to solution B, and through two recrystallization processes, the product (NH₄)₃[CoMo₆O₂] is obtained. 24 H6].

[0056] Synthesis of the catalytic material: In air, 200 mg of polyethyleneimine (PEI) was placed in a beaker containing 100 ml of water and sonicated for 30 min to dissolve, forming a PEI aqueous solution; the PEI aqueous solution was added dropwise to a beaker containing 100 ml of 2 mg / mL graphene oxide aqueous solution and stirred for 6 h; the synthesized PEI / GO solution was filtered, washed, and dissolved in 110 ml of water; 100 mg of (NH4)3[CoMo6O 24 [H6] The polyacid material was dissolved in 10 ml of water and then added dropwise to the PEI / GO aqueous solution. The mixture was sonicated for 2 h. After hydrothermal treatment at 180 °C for 720 min, the mixture was filtered, washed, and freeze-dried at -50 °C for 48 h. Finally, it was heat-treated at 600 °C under H2 / Ar atmosphere for 2 h to obtain the composite material Co-MoOx / rGO / C, which is a single-atom substituted Mo oxide, reduced graphene oxide, and a small amount of carbon. Membrane preparation: 28.26 mg of Co-MoOx / rGO composite material and 62.8 mg of LA (5% LA, mass ratio 9:1) were mixed in 10 ml of alcohol solution by sonication for 1 h. The mixture was then filtered onto a Celgard 2500 polypropylene microporous membrane with a loading of 0.5 mg / cm³. 2 The material was dried in an oven for 12 hours, then removed and cut into 19 mm diaphragms. The schematic diagram of the preparation principle of the electrocatalyst based on polyacid materials is shown below. Figure 1 As shown.

[0057] Positive electrode sheet production: Same as comparative example 1.

[0058] Battery assembly: The assembly method is the same as that of Comparative Example 1, wherein the separator used is the Co-MoOx / rGO / C composite separator prepared in Example 1.

[0059] Comparative Example 3 (One-pot preparation of Co-MoOx / rGO / C) Synthesis of catalyst materials: In air, 30 ml of cobalt sulfate solution (containing 4.2 g CoSO4·7H2O, 0.015 mol) is mixed with 2 g of hydrogen peroxide solution (concentration 30%) to form mixed aqueous solution A; ammonium heptamolybdate aqueous solution (containing (NH4)6Mo7O) is mixed with... 24· 0.9 g of 4H2O (0.025 mol, 260 mL of H2O) was heated to boiling to form solution B; 200 mg of polyethyleneimine (PEI) was placed in a beaker containing 100 mL of water to form solution C; 100 mL of 2 mg / mL graphene oxide aqueous solution was placed in a beaker to form solution D; solutions A, B, C, and D were mixed at once and sonicated for 2 h; hydrothermally heated at 180 °C for 720 min, filtered and washed, freeze-dried at -50 °C for 48 h, and then heat-treated at 600 °C under H2 / Ar atmosphere for 2 h to obtain the Co-MoOx / rGO / C composite material.

[0060] Figure 2 and Figure 3 The images show a TEM comparison of the catalyst material prepared in Example 1 and the catalyst material prepared by the one-pot method in Comparative Example 1. As can be seen from the images, the catalyst material prepared by the one-pot method exhibits a large number of agglomerates, and the loaded polyacid salts are not visible, indicating extremely poor dispersibility and a lack of obvious active sites. In contrast, the catalyst material prepared in Example 1 has a clear structure, with a large number of individual particles loaded on the rGO surface, exhibiting excellent dispersibility and abundant active sites. Analysis suggests that these particles may be polyacid salts substituted with individual metal atoms, resulting in excellent dispersibility and abundant active sites.

[0061] Comparative Example 4 Synthesis of catalyst materials: The only difference between this comparative example and Example 1 is that the heat treatment and hydrothermal steps are omitted in the catalyst synthesis process.

[0062] Synthesis of the catalytic material: In air, 200 mg of polyethyleneimine (PEI) was placed in a beaker containing 100 ml of water and sonicated for 30 min to dissolve, forming a PEI aqueous solution; the PEI aqueous solution was added dropwise to a beaker containing 100 ml of 2 mg / mL graphene oxide aqueous solution and stirred for 6 h; the synthesized PEI / GO solution was filtered, washed, and dissolved in 110 ml of water; 100 mg of (NH4)3[CoMo6O 24 [H6] The polyacid material was dissolved in 10 ml of water and then added dropwise to the PEI / GO aqueous solution. After sonication for 2 h, it was filtered and washed, and then freeze-dried at -50℃ for 48 h to obtain the composite catalyst material.

[0063] Membrane preparation: Same as Comparative Example 1, except that the catalytic material used is the composite catalytic material prepared in Comparative Example 4.

[0064] Positive electrode sheet production: Same as comparative example 1.

[0065] Battery assembly: The assembly method is the same as that of Comparative Example 1, but the separator used is the composite catalytic material composite separator prepared in Comparative Example 4.

[0066] Comparative Example 5 Synthesis of catalyst materials: The only difference between this comparative example and Example 1 is that the heat treatment step is omitted in the catalyst synthesis process.

[0067] Synthesis of the catalytic material: In air, 200 mg of polyethyleneimine (PEI) was placed in a beaker containing 100 ml of water and sonicated for 30 min to dissolve, forming a PEI aqueous solution; the PEI aqueous solution was added dropwise to a beaker containing 100 ml of 2 mg / mL graphene oxide aqueous solution and stirred for 6 h; the synthesized PEI / GO solution was filtered, washed, and dissolved in 110 ml of water; 100 mg of (NH4)3[CoMo6O 24 [H6] The polyacid material was dissolved in 10 ml of water and then added dropwise to the PEI / GO aqueous solution. The mixture was sonicated for 2 h. After hydrothermal treatment at 180 °C for 720 min, the mixture was filtered, washed, and freeze-dried at -50 °C for 48 h to obtain the composite catalyst material.

[0068] Membrane preparation: Same as Comparative Example 1, except that the catalytic material used is the composite catalytic material prepared in Comparative Example 5.

[0069] Positive electrode sheet production: Same as comparative example 1.

[0070] Battery assembly: The assembly method is the same as that of Comparative Example 1, but the separator used is the composite catalytic material composite separator prepared in Comparative Example 5.

[0071] Example 2 Preparation of polyacid materials: Nickel sulfate aqueous solution (0.87g NiSO4·7H2O, 3.1*10) -3 5.19 g of (NH4)6Mo7O (mol, 20 ml water) was added to a boiling aqueous solution of ammonium heptamolybdate (containing 5.19 g of (NH4)6Mo7O). 24 ·4H2O, 4.2*10 -3 The solution was thoroughly mixed with 80 ml of water (mol), then evaporated in a water bath for 6 hours. The hot solution was filtered and cooled to obtain the product (NH4)4[Ni(II)Mo6O]. 24 H6].

[0072] Synthesis of catalytic materials: The synthesis process of PEI / GO solution is the same as in Example 1. After filtration and washing, it is dissolved in 110 ml of water; take 100 mg of (NH4)3[NiMo6O 24 [H6] The polyacid material was added dropwise to PEI / GO aqueous solution in 10 ml of water and sonicated for 2 h; hydrothermally heated at 180℃ for 720 min, filtered and washed, freeze-dried at -50℃ for 48 h, and then heat-treated at 600℃ in H2 / Ar atmosphere for 2 h to obtain Ni-MoOx / rGO / C composite material.

[0073] Membrane preparation: 28.26 mg of Ni-MoOx / rGO / C composite material and 62.8 mg of LA (5% LA, mass ratio 9:1) were mixed in 10 ml of alcohol solution by ultrasonication for 1 h. The mixture was then filtered onto a Celgard 2500 polypropylene microporous membrane with a loading of 0.5 mg / cm³. 2 Dry in an oven for 12 hours, then remove and cut into 19 mm diaphragms.

[0074] Positive electrode sheet production: Same as comparative example 1.

[0075] Battery assembly: The assembly method is the same as that of Comparative Example 1, but the separator used is the Ni-MoOx / rGO composite separator prepared in Example 2.

[0076] Example 3 The catalyst preparation differs from that in Example 1 only in the use of a different polyacid material; the polyacid material is [CuMo6O] substituted with Cu. 24 ] n- The final product obtained from the polyacid material is a Cu-MoOx / rGO / C composite material.

[0077] Preparation of polyacid materials: Copper sulfate aqueous solution (0.75g CuSO4·5H2O, 3.0*10) -3 5.19 g of (NH4)6Mo7O (mol, 20 mL water) was added to a boiling aqueous solution of ammonium heptamolybdate (containing 5.19 g of (NH4)6Mo7O). 24 ·4H2O, 4.2*10 -3 The solution was thoroughly mixed with an aqueous solution of (1 mol, 80 mL water) and evaporated in a water bath for 6 h. The hot solution was then filtered and cooled to obtain the product (NH4)4[Cu(II)Mo6O] 24 H6].

[0078] The preparation of the separator, the preparation of the positive electrode, and the assembly of the battery are the same as in Example 1.

[0079] Example 4 The catalyst preparation differs from that in Example 1 only in the use of a different polyacid material; the polyacid material is [ZnMo6O] substituted with Zn. 24 ] n- The resulting product from the polyacid material is a Zn-MoOx / rGO / C composite material.

[0080] Preparation of polyacid materials: A zinc sulfate aqueous solution (containing 0.86 g ZnSO4·7H2O, 3.0*10) was prepared. -3 5.19 g (NH4)6Mo7O (mol, 20 mL H2O) was added to a boiling solution of heptamolybdate (containing 5.19 g (NH4)6Mo7O). 24 ·4H2O, 4.2*10 -3The solution was thoroughly mixed with 80 mL of H₂O and evaporated in a water bath for 6 hours. The hot solution was then filtered and cooled to obtain the product (NH₄)₄[Zn(II)Mo₆O₆]. 24 H6].

[0081] The preparation of the separator, the preparation of the positive electrode sheet, and the battery assembly are the same as those in Comparative Example 1.

[0082] Example 5 The catalyst preparation differs from that in Example 1 only in the polyacid material; the polyacid material is [FeMo6O] substituted with Fe. 24 ] n- The polyacid material ultimately yields a Fe-MoOx / rGO / C composite material.

[0083] Preparation of polyacid materials: Ferric sulfate aqueous solution (containing 1.2g ferric sulfate, 3.0*10...) -3 5.19 g of (NH4)6Mo7O (mol, 20 ml water) was added to a boiling aqueous solution of ammonium heptamolybdate (containing 5.19 g of (NH4)6Mo7O). 24 ·4H2O, 4.2*10 -3 The solution was thoroughly mixed in 80 ml of H2O and then evaporated in a water bath for 6 hours. The hot solution was filtered and cooled to obtain the product (NH4)3[Fe(Ⅲ)Mo6O] 24 H6].

[0084] The preparation of the separator, the preparation of the positive electrode sheet, and the battery assembly are the same as those in Comparative Example 1.

[0085] Example 6 The catalyst preparation differs from that in Example 1 only in the use of a different polyacid material; the polyacid material is [MnMo6O] substituted with Mn. 24 ] n- The final product obtained from the polyacid material is a Mn-MoOx / rGO / C composite material.

[0086] Preparation of polyacid materials: Manganese sulfate aqueous solution (containing 0.45g manganese sulfate, 3.0*10...) -3 5.19 g (NH4)6Mo7O (20 ml water) was added to a room temperature ammonium heptamolybdate aqueous solution (containing 20 ml water). 24 ·4H2O, 4.2*10 -3 (mol, 80ml water), after thorough mixing, filtered to obtain the product (NH4)4[Mn(II)Mo6O 24 H6].

[0087] The preparation of the separator, the preparation of the positive electrode sheet, and the battery assembly are the same as those in Comparative Example 1.

[0088] Example 7 The catalyst preparation differs from that in Example 1 only in the polyacid material; the polyacid material is [PtMo6O] substituted with Pt. 24 ] n- The polyacid material ultimately yields a Pt-MoOx / rGO / C composite material.

[0089] Preparation of polyacid materials: A sulfate aqueous solution (containing 1.08 g tetraammineplatinum sulfate, 3.0 * 10) was prepared. -3 5.19 g (NH4)6Mo7O (20 ml water) was added to a boiling aqueous solution of ammonium heptamolybdate (containing 20 ml water). 24 ·4H2O, 4.2*10 -3 After thorough mixing with 80 ml of water, the mixture was evaporated in a water bath for 6 hours. The hot solution was then filtered and cooled to obtain the product (NH4)4[Pt(II)Mo6O] 24 H6].

[0090] The preparation of the separator, the preparation of the positive electrode sheet, and the battery assembly are the same as those in Comparative Example 1.

[0091] The electrochemical performance of the batteries assembled in Examples 1, 2, 1, and 2 was tested in the following manner: After assembly, the batteries were left to stand for 2 hours, and then the charge-discharge cycle electrochemical performance of the batteries was tested using a multi-channel battery tester. The cycle test voltage range was 1.7-2.7 V, the current density was 1 A / g (1C), and the test temperature was room temperature.

[0092] Figure 4 shows the cycle performance curve of the battery assembled in Comparative Example 1. After 50 cycles, the battery failed and could not continue cycling.

[0093] Figure 5 shows the cycle performance curve of the battery assembled in Comparative Example 2. After 100 cycles, the capacity is 678.8 mAhg. -1 The capacity retention rate was 64.6%.

[0094] Figure 6 shows the cycle performance curve of the battery assembled in Example 1. After 100 cycles, the capacity is 932.1 mAhg. -1 The capacity retention rate was 88.7%, indicating that the battery has high capacity and cycle performance, demonstrating that the catalytic material has a good catalytic effect. Analysis shows that this is because, on the one hand, the substitution of single atoms in the prepared catalytic material improves the catalytic activity of the structure; on the other hand, the substitution of single atoms achieves good dispersion, resulting in high catalytic efficiency and high battery capacity. Furthermore, the catalytic material has good structural stability, which allows it to maintain good catalytic stability during cycling, thus achieving good cycle performance.

[0095] Figure 7The figure shows the cycle performance curves of the battery assembled in Comparative Example 4. As can be seen from the figure, the Co-MoOx / GO without hydrothermal and firing processes cannot achieve its capacity when cycled at 1C. Analysis suggests that this may be because the Co-MoOx / GO material without heat treatment has a higher density, which, after modification of the separator, would hinder the ion channels in the PP separator, preventing the migration of lithium ions from the negative electrode, thus preventing the battery reaction from proceeding and the capacity from being fully utilized.

[0096] Figure 8 The figure shows the cycle performance curve of the battery assembled in Comparative Example 5. As can be seen from the figure, the battery assembled with the catalyst material obtained by hydrothermal treatment but without sintering failed after more than 10 cycles at 1C. Analysis suggests that this may be because the internal structure of the un-sintered catalyst material is unstable. During the cycle, the structure collapses when repeated battery reactions occur, resulting in a significant reduction in capacity and substantial damage to the battery.

[0097] Figure 9 shows the cycle performance curve of the battery assembled in Example 2. After 100 cycles, the capacity is 913.3 mAhg. -1 The capacity retention rate was 87.7%.

[0098] Figure 10 The images show a comparison of the SEM images of the positive and negative electrodes of Comparative Example 1 and Example 1 after 200 cycles at 1C. (a) and (b) are microscopic morphology images of the positive electrode surface of the batteries of Example 1 and Comparative Example 1 after 200 cycles at 1C, respectively: it is clear that the electrode surface of the battery of Example 1 after 200 cycles is smooth and dense, while the electrode surface of the battery of Comparative Example 1 after 200 cycles is relatively rough, which is attributed to the uneven deposition of lithium sulfide. (c) and (d) are microscopic morphology images of the lithium negative electrode surface of the batteries of Example 1 and Comparative Example 1 after 200 cycles, respectively: after 200 cycles, the lithium negative electrode surface of Comparative Example 1 shows severe pulverization, severe lithium sheet corrosion, and clearly visible cracks. The results indicate that the electrocatalyst material based on polysulfide-derived materials prepared in this invention can significantly suppress the shuttle effect of soluble polysulfides during cycling and effectively avoid side reactions between polysulfides and the negative electrode.

[0099] Figure 11 The images show different materials reacting with Li₂S₆ for the same amount of time. 5 mg of Ni-MoOx / rGO, Co-MoOx / rGO, and rGO powder were added to Li₂S₆ solutions of the same concentration, respectively, and the solutions were shaken and allowed to stand. After standing for 12 hours, the Li₂S₆ solutions with added Ni-MoOx / rGO and Co-MoOx / rGO powders were nearly colorless, while the Li₂S₆ solution with added rGO remained yellow. This fully demonstrates that the electrocatalyst material based on polyacid materials prepared in this invention has a strong interaction with soluble polysulfides.

[0100] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries, characterized in that, include: First, a single-atom-substituted polyacid material is prepared by substituting a polyacid or polyacid salt with a single metal atom X. Then, a cationic linker is assembled with graphene oxide and the single-atom-substituted polyacid material in an aqueous solution, so that the single-atom-substituted polyacid material is loaded on the surface of graphene oxide. A hydrothermal reaction is then carried out, followed by solid-liquid separation, freeze-drying, and low-temperature heat treatment to obtain a polyacid-derived electrocatalyst for lithium-sulfur batteries. The single atom X is selected from one of Co, Ni, Cu, Zn, Fe, Mn, Ag, Au, Pt, Pd, Ru, and Ir. The anion of the single-atom-substituted polyacid material is selected from [PMo]. 11 XO 40 ] n- [SiMo] 11 XO 40 ] n- [PW] 11 XO 40 ] n- 、[SiW 11 XO 40 ] n- and [XMo6O 24 H6] n- At least one of the following: the cationic binder is selected from at least one of dopamine and polyethyleneimine; the temperature of the low-temperature heat treatment is 200~600℃; the atmosphere of the low-temperature heat treatment is a hydrogen-argon mixture.

2. The method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries as described in claim 1, characterized in that, The cation in the monoatom-substituted polyacid material is selected from H. + Li + Na + K + and NH4 + At least one of them.

3. The method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries as described in claim 1, characterized in that, The mass ratio of the cationic binder, graphene oxide, and monoatom-substituted polyacid material is 4:4:1 to 1:1:

1.

4. The method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries as described in claim 1, characterized in that, The hydrothermal reaction temperature is 100~200℃ and the hydrothermal reaction time is 6~24 h.

5. The method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries as described in claim 1, characterized in that, The freeze-drying temperature is -80 to -40°C; the freeze-drying time is 12 to 72 hours.

6. The method for preparing a polyacid-derived electrocatalyst for lithium-sulfur batteries as described in claim 1, characterized in that, The assembly process involves stirring or ultrasonically treating the mixed liquid; the stirring or ultrasonic treatment time is 1-2 hours.

7. A polyacid-derived electrocatalyst for lithium-sulfur batteries, prepared by the preparation method described in any one of claims 1 to 6.

8. The application of the polyacid-derived electrocatalyst for lithium-sulfur batteries as described in claim 7, characterized in that, The electrocatalyst was ultrasonically dispersed in an ethanol solution to form a slurry, and then vacuum filtration was used to uniformly modify the catalyst material onto the lithium-sulfur battery separator.

9. The application as described in claim 8, characterized in that, The electrocatalyst has an areal loading of 0.25~5 mg / cm³ on the lithium-sulfur battery separator. 2 ; The slurry concentration of the electrocatalyst is 2~20 mg / mL; The lithium-sulfur battery separator is at least one of polyethylene (PE) separator or polypropylene (PP) separator.

Citation Information

Patent Citations

  • Preparation method of polyacid-derived atomic-scale doped molybdenum nitride electrocatalyst

    CN114457378A

  • Electrocatalytic material and preparation method thereof, isolating membrane and lithium-sulfur battery

    CN115555026A